The contribution of human resources from graduates of Sharia Economics Science Colleges to the stakeholders of Baitul Maal wa Tamwil in Tulungagung - Sulchan, Moch (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2024)
Abstract The rapid growth of sharia financial institutions, especially non-bank financial institutions, has increased the need for SDI with sharia economics expertise. As more people graduate from sharia economics colleges, financial firms can only accommodate a tiny number. Even though sharia economics knowledge is preferred when hiring, many sharia financial firms nevertheless hire non-sharia economists. This study examines if sharia economics college graduates can meet BMT's SDI requirements in Tulungagung. Can BMT's sharia economic SDI improve institutional progress. How do BMT stakeholders see sharia economic SDI contributions. This study seeks to determine if sharia economics university graduates meet BMT-BMT in Tulungagung's SDI requirements. To determine whether SDI improves BMT. Determine BMT stakeholders' reaction to sharia economic human resources inputs. This study follows a qualitative descriptive technique. Data is collected via interviews and documentation. Researchers employed interviews and paperwork to gather data on sharia economics human resources' impact on financial institution stakeholders, particularly BMT in Tulungagung. The study found that Baitul Maal wa Tamwil stakeholders welcomed sharia economics graduates since they had been waiting for SDIs with economics and sharia skills. SDIs' competences do not fulfill BMT's requirements, yet they still hire many people without sharia economics degrees as long as they have the right experience and skills. Keywords : Contribution, HR, Baitul Maal wa Tamwil